The Projections of Convex Lattice Sets of Points in E2. (15th November 2016) - Gu, Yu; Si, Lin
Abstract : Can one determine a centrally symmetric lattice polygon by its projections? In 2005, Gardner et al. proposed the above discrete version of Aleksandrov's projection theorem. In this paper, we define a coordinate matrix for a centrally symmetric convex lattice set and suggest an algorithm to study this problem.